Tenets of Poetics on As You Like It - Kandel, Churamoni (Dristikon: A Multidisciplinary Journal, 2025)
This study delves into the application of Aristotle's Poetics within Shakespeare's play, As You Like It. Through a qualitative exploration, it investigates the play's adherence to the fundamental principles outlined in Poetics, analyzing the aspects like plot structure, character development, diction, and thematic expression. Shakespeare, in his characteristic dramatic style, intertwines elements of comedy, romance, and realism, ultimately resolving conflicts through matrimonial unions. The play introduces central characters such as Rosalind, Orlando, Oliver, and Celia to navigate the intricate web of relationships. The main plot revolves around the love between Rosalind and Orlando, while sub-plots involving Silvius-Phoebe-Ganymede, Touchstone-Audrey, and Celia-Oliver add depth to the narrative. Shakespeare employs both verse and prose in this play, with poetic eloquence in Duke Senior’s reflections and Jaques’ famous “seven ages of man” speech. His witty wordplay and antitheses in the prose sections add a distinct charm to the play’s dialogue. Natural imagery, particularly within the Forest of Arden, enriches the pastoral setting, invoking images of trees, brooks, animals, and aspects of rural life. Thematically, the play explores love, injustice, usurpation, loyalty, forgiveness, and reconciliation. Through this analysis, As You Like It emerges as a compelling embodiment of Aristotle's Poetics, blending entertainment with philosophical inquiry and providing a timeless reflection on human nature and social harmony.